2013
DOI: 10.1186/1752-1947-7-196
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular tachycardia – an atypical initial presentation of sarcoidosis: a case report

Abstract: IntroductionSymptomatic cardiac involvement is seen in less than 5% of all cases of sarcoidosis. Although clinically apparent cardiac sarcoidosis is an uncommon entity, ventricular tachyarrhythmias as the first presenting symptom are very rare.Case presentationWe discuss the case of a 41-year-old Asian woman who presented to our hospital with intermittent palpitation and on evaluation was diagnosed to have systemic sarcoidosis with cardiac involvement. She was started on multiple antiarrhythmic drugs and corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In another study, a 41-year-old lady presented with VT and was found to have systemic sarcoidosis with cardiac involvement; she was started on steroids, amiodarone, and metoprolol, and received failed radiofrequency ablation. Unfortunately, the patient passed away due to recurrent VT [ 7 ]. Therefore, maintaining a high index of early suspicion of sarcoidosis in patients presenting with arrhythmias, especially in the absence of CAD, is critical to prevent disease-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a 41-year-old lady presented with VT and was found to have systemic sarcoidosis with cardiac involvement; she was started on steroids, amiodarone, and metoprolol, and received failed radiofrequency ablation. Unfortunately, the patient passed away due to recurrent VT [ 7 ]. Therefore, maintaining a high index of early suspicion of sarcoidosis in patients presenting with arrhythmias, especially in the absence of CAD, is critical to prevent disease-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The course of sarcoidosis can be silent, but serious complications in cardiac sarcoidosis can lead to sudden cardiac death. Cardiac involvement is an independent cursor of mortality and associated with poor survival [2].…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids should be administered in doses of 1mg/kg/day, and then tapered after 2-3months, to 10-20mg every other day. [20][21][22][23][24][25][26][27][28] ICD placement should be strongly considered in this population, especially in patients with evidence of extensive myocardial damage and fibrosis or in the presence of arrhythmias, as studies have shown an increased rate of adverse events and sudden cardiac death. As such, placement of an ICD for primary prevention is a Class IIa recommendation.…”
Section: Treatmentmentioning
confidence: 99%